Dynamic System Analysis of Vannamei Shrimp Supply Chain: Evaluation of Distribution Delays in Cold Chain Logistics at Exporting Companies - Nurhijriani Kasim; Yudha Prambudia; Iphov Kumala Sriwana (LP2M IAIN Palopo, 2025)
Vannamei shrimp is one of Indonesia's leading export commodities that relies heavily on the efficiency of cold chain logistics to maintain product quality during shipping. Purpose: This study aims to analyze the factors causing distribution delays in the vannamei shrimp supply chain at a seafood exporting company in Makassar, South Sulawesi, and evaluate their impact on product quality, return rates, and export prices. Methods: The method used is the System Thinking and System Dynamics approach, by building a dynamic system model using Vensim software. Data were obtained through literature studies, interviews, field observations, and historical distribution data for 2023. Results: The results show that an average distribution delay of 12–18 hours causes an increase in temperature during transportation by 2–3°C, resulting in a decrease in shrimp quality and an increase in return rates of up to 7% of total monthly exports. Through simulations of improvement scenarios, the model shows that optimizing the criteria for export-worthy shrimp and increasing the efficiency of distribution rates can reduce the number of damaged shrimp and increase export volume. Model validation tests with a MAPE value of 5.16% indicate a good match between the simulation results and actual conditions in the field. Implications: This research is expected to be a reference for exporting companies in designing strategies to improve cold chain logistics to increase the competitiveness of Indonesian shrimp products in the international market.